An overview of riverbank erosion prediction techniques applied to the Mekong Delta, Vietnam - Pham Ngoc Thinh (E3S Web of Conferences, 2024)
In recent times, the Mekong Delta has been experiencing severe riverbank erosion, causing significant damage to property, homes, land, and riverside infrastructure. The region is facing increasing intensity of erosion events, attributed to the impact of climate change and the effects of hydropower dams and water control systems upstream on the Mekong River. This paper discusses five key methodologies currently applied for riverbank erosion prediction in the Mekong Delta: digital map overlay, historical topographic data analysis, geophysical and terrain change analysis, physical phenomenon simulation using analogous conditions, and empirical formula-based prediction. Each method's theoretical foundation, procedural steps, and potential limitations are explored in depth.